A supply chain vulnerability map for the automotive and electronic industries in Brazil / Mauricio F. Blos and Hui-Ming Wee - F. Blos, Mauricio; Wee, Hui-Ming (Universiti Teknologi MARA Cawangan Sarawak, 2018)
This paper aims to explore various perspectives of the Supply Chain Risk Management (SCRM) as they relate to the automotive and electronic industries in Brazil based on the historical data from 2010 to 2016. The methodological approach was based on the Supply Chain Vulnerability Map (SCVM). The SCVM was tested in its totaliness and two more risks were added to the hazard vulnerability category to form the SCVM II. The exploratory surveys were used to better understand the impacts on the automotive and electronic industries in Brazil during the study period. An interesting finding was that most of the major automotive and electronic industries are concerned with integrating risk management, governance and compliance in the supply chain. The findings of the empirical investigation and SCRM historical data indicate that managers must integrate risk management, governance and compliance in the supply chain and use the proposed SCVM II. This research revealed the risks that surrounded the supply chain during the time period covered. In the study, the researchers added two more risks to the hazard vulnerability category: item 10, deficient rainfall (as seen in Manaus and São Paulo) and number 13, viral epidemics (to reflect the Zika virus around Brazil), it was named as SCVMII. Among the limitations of the research was that the study applied real data which might vary drastically due to economic downturn of the country. This might affect the performance of the investigated industries